THE EFFECT OF GRDP, MINIMUM WAGE, AND THE NUMBER OF INDUSTRIAL ENTERPRISE UNITS ON LABOR ABSORPTION IN THE MANUFACTURING SECTOR IN LAMPUNG PROVINCE 2017-2022 - Ferdi Septiawan Perdana; Toto Gunarto (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The manufacturing industry plays an important role in the economy as a leading sector and as a provider of employment for the population to meet the job market. This research aims to analyze the influence of the manufacturing industry sector in absorbing labor. The variables used include Gross Regional Domestic Product (GRDP) of the manufacturing industry sector, minimum wage in Regencies/Cities, the number of manufacturing industry units in absorbing labor in the manufacturing industry sector in the Lampung Province during the period of 2017-2022. The analytical methodology used is the panel data regression analysis method using classic assumption testing, model suitability testing, t-test and f-test hypothesis testing, and coefficient of determination analysis. The results show that GRDP of the manufacturing industry sector and the number of manufacturing industry units have a positive and significant influence on labor absorption, while minimum wage in regencies/cities has a negative and significant influence on labor absorption in the Lampung Province during the period of 2017-2022